2022
DOI: 10.1093/tas/txac020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of enhanced Escherichia coli phytase on growth performance, bone quality, nutrient digestibility, and metabolism in nursery pigs fed corn-soybean meal diet low in calcium and digestible phosphorous

Abstract: Efficacy of Aspergillus niger phytase (ASP) was evaluated in nursery pigs fed low Ca and digestible P corn and soybean meal diet. Piglets were weaned on d 21, fed a common commercial starter diet for 7 d and assigned to pens (4 pigs/pen: 2 ♀ and 2 ♂) based on BW on d 7. Positive control (PC) and negative (NC) diets were formulated with similar energy and nutrients with exception of total Ca, total P and digestible P concentrations being 79%, 67%, and 55% that of PC diet, respectively. Two other diets were form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…Differences in serum Ca concentrations coincided with differences in urinary Ca excretion, which is consistent with the results of Schlegel and Gutzwiller (2017) . The serum ALP activity was decreased with the addition of phytase, which is consistent with the study of Kiarie et al (2022) , who observed a decrease in plasma ALP activity in nursery pigs with the addition of exogenous phytase to a low-P corn-based diet. The calculated hindgut disappearance of P and Ca did not differ, and the values were close to zero, indicating no net absorption of these minerals in the hindgut.…”
Section: Discussionsupporting
confidence: 90%
“…Differences in serum Ca concentrations coincided with differences in urinary Ca excretion, which is consistent with the results of Schlegel and Gutzwiller (2017) . The serum ALP activity was decreased with the addition of phytase, which is consistent with the study of Kiarie et al (2022) , who observed a decrease in plasma ALP activity in nursery pigs with the addition of exogenous phytase to a low-P corn-based diet. The calculated hindgut disappearance of P and Ca did not differ, and the values were close to zero, indicating no net absorption of these minerals in the hindgut.…”
Section: Discussionsupporting
confidence: 90%
“…Enzyme-treated GRP pomace had a significantly higher plasma ALP compared to the rest of the enzyme-treated and non-enzyme-treated pomaces. Increase in plasma ALP has also been noted in pigs fed diets supplemented with phytase enzyme linked with increased bone mineralization (Kiarie et al 2022). Additionally, there were non-significant differences in ALP levels between the enzymetreated and non-enzyme-treated pomaces.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, P is an indispensable nutrient needed for normal growth, and it plays important roles in vital functions, such as energy and amino acid metabolism, protein synthesis, and maintaining acid–base balance [ 27 , 28 , 29 , 30 ]. Several studies have reported improvements in performance when phytase was used in piglets and growing pigs [ 21 , 31 , 32 , 33 , 34 , 35 ]. In the current study, the addition of phytase at 500 FTU/kg diet improved the growth performance and feed efficiency of nursery and growing–finishing pigs fed diets reduced in digestible P and Ca.…”
Section: Discussionmentioning
confidence: 99%